Knowledge, attitude and practice of over the counter analgesic among undergraduate students in health campus USM - Amin, Siti Nur'Ain Suraya Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Over-the-Counter (OTC) analgesics is one of the convenient and effective treatments for pain used in both develop and developing countries. However, this treatment could lead to the dangerous effect and complication depending on how we utilize it. A cross sectional study was conducted on Medical, Dental and Nursing students in health Campus, USM to determine the level of knowledge, attitude and practice related to OTC analgesics. This study also aimed to identify the association of sociodemographic data with knowledge level by using Fisher Exact Test and Pearson Chi Square. This study also aimed to determine the correlation between knowledge, attitude and practice on OTC analgesic. Therefore, Pearson Correlation test was used for this objective. Out of 285 undergraduate students, 199 from Medical, 53 from Dental and 33 from nursing were selected through simple random sampling technique. The data was run in SPSS the was using SPSS version 26. Most of the students are female students (58.2). The finding shows that undergraduate students in Health Campus USM were having a moderate knowledge level (M = 5. 91, SD=1.048). As for the attitude and practice level, the score revealed 60.4% students with good attitude (M= 23.93, SD=3.195) and 61.4% students with fair practice (M= 20.26, SD 3.526). There was no relationship of any sociodemographic data to be found significant. On the other hand, the knowledge has significant relationship with (r = 0. 292, p value < 0.001). attitude, and attitude also shows significant relationship with practice (r = 0. 220, p value < 0.001). In conclusion, students’ knowledge needs to be enhanced to improve the awareness on safe medication practice.